Protein dan Asam Amino pada Edible Sargassum aquifolium, Ulva lactuca, dan Gracilariopsis longissima: Protein and Amino Acid of Edible Sargassum aquifolium, Ulva lactuca and Gracilariopsis longissima - Alberta Rika Pratiwi; Irma Fadlilah; Victoria Kristina Ananingsih; Meiliana Meiliana (Jurnal Pengolahan Hasil Perikanan Indonesia, 2021)
Seaweed or macroalgae have been used by the food industry for a long time because of the components they contain such as alginate, carrageenan, and agar. In addition, seaweed contains nutrients and other bioactive components which makes seaweed a functional food. Information about its protein content and amino acid diversity is important to maximize seaweed’s potential. This study aimed to determine the protein content and amino acid profile of S. aquifolium, U. lactuca, and G. longissima. Protein was extracted using 0.4 M NaOH solvent and ultrasonication for 5 minutes with an amplitude of 70% and analyzed with the Bradford method. The amino acid composition was analyzed using ultra performance liquid chromatography. S. aquifolium had the highest protein content (4.17%) and 16 types of amino acids, which consist of 10 essential amino acids (AAEs) and 6 non-essential amino acids (AANEs). U. lactuca had 9 AAEs and 6 AANEs, while G. longissima had 8 types of AAEs and 6 types of AANEs. Glutamic acid was the highest amino acid in S. aquifolium (400.27±62.27 mg/kg), while aspartic acid was the highest in U. lactuca (274.60±50.14 mg/kg) and G. longissima (435.57±25.81mg/kg). Edible macroalgae contain protein and many types of amino acids, and some have higher concentrations than similar macroalgae protein sources from other water areas. The amino acids possessed by these three macroalgae have the potential to be further developed into plant-based food products with umami flavor and taste characteristics, such as vegetables, spices, or any processed food products.